PEDAGOGI, KEKUATAN DAN TANTANGAN BAGI TRANFORMASI PENDIDIKAN PESANTREN - Adri Lundeto (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
The splendor or collapse of a nation depends on the nation's education. Santri are expected to have a good personality through religious teaching. Religious education seeks to shape human excellence and lead to a worldly attitude to God and future happiness. This study uses a qualitative methodology as a descriptive analysis research. Philosophical and pedagogical approaches are applied to understand the topic of study more fully. Content analysis technique is data analysis used in this research. The transformation of education in Islamic boarding schools can be traced through integrating Islamic education and other fields of science, revolutionizing and reforming teaching and learning activities in Islamic education by bringing the noble values of Islam into real life, reformulating learning materials in Islamic education, and transforming and internalizing Islamic education.